Analysis Of Drug Inventory Accounting Based On Psap No. 5 At Tungkal 1 Public Health Center, Pino Raya District - Sagita, Nabila Dayana; Hidayah, Nenden Restu; Astuty, Kamelia (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze the implementation of drug inventory accounting based on PSAP No. 5 at Tungkal 1 Public Health Center, Pino Raya District. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The data were analyzed by comparing the accounting practices at the health center with the provisions of PSAP No. 5 regarding recognition, measurement, presentation, and disclosure of inventories. The results show that the implementation of drug inventory accounting at Tungkal 1 Health Center is partially in accordance with PSAP No. 5. The recognition process has been properly carried out when the drugs are received, but the measurement, presentation, and disclosure are not yet in accordance with the standard due to manual recording and the absence of value data. It is suggested that the health center adopt a computer-based accounting system to improve the accuracy and accountability of inventory management.